IGFBP1 in epithelial circulating tumor cells as a potential response marker to selective internal radiation therapy in hepatocellular carcinoma. (June 2014) - Nel, Ivonne; Baba, Hideo A; Weber, Frank; Sitek, Barbara; Eisenacher, Martin; Meyer, Helmut E; Schlaak, Joerg F; Hoffmann, Andreas-Claudius
Background: Local ablative techniques such as selective internal radiation therapy (SIRT) have become the mainstay of treating hepatocellular carcinoma (HCC) in the bridging-to-transplant and palliative setting. We recently demonstrated that epithelial circulating tumor cells (CTCs) correlate to an unfavorable outcome. We wanted to scrutinize whether molecular markers detected in this specific CTC subgroup may also have clinical implications.Materials & methods: Mononuclear cells and CTCs were isolated from peripheral blood samples using density gradient centrifugation followed by depletion of hematopoietic and enrichment of epithelial (EpCAM + ) cells employing immunomagnetic beads. The mRNA expression of candidate markers was correlated with response to SIRT in 25 patients using quantitative real-time reverse-transcription PCR.Results: IGFBP1 mRNA expression levels were significantly correlated with time to progression in a Kaplan–Meier log rank test (p = 0.04; 0 vs 4 months) and receiver operating characteristic analysis demonstrated a potential use to predict patients with shortened time to progression (area under the curve: 0.8; 95% CI: 0.44–0.98; p = 0.03).Conclusion: The EpCAM fraction of CTCs may be useful to detect novel molecular markers to individualize treatment decision in patients with HCC.